The labour market in Kazakhstan under conditions of active transformation of their economy - Ansagan Beisembina; George Abuselidze; Begzat Nurmaganbetova; Gulnur Kabakova; Aigul Makenova; Ainash Nurgaliyeva (Economies, 2025)
Continuous transformations, which have been observed more and more in recent years, require an increase in the effectiveness of measures in the state regulation of the labour market, which is possible only with a clear understanding and realistic assessment of its condition and existing trends of changes. For this purpose, guided by the data of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan, the country's labour market was monitored, and the key factors that played a significant role in its formation were identified. Using these factors as a basis, vector autoregression (VAR) models were built to analyse dynamic relationships between economic variables. The choice of stationary variables ensured the adequacy of the model, which was confirmed by diagnostic tests such as the ADF test, Jarque-Bera test, and Ljung-Box test. Impulse response functions (IRFs) were used to assess the effect of shocks on each variable and other system variables. All results were visualised as graphs illustrating the dynamics of the impact over ten times. The modelling results showed that the changes are interrelated: shocks to youth unemployment (YUR) have the most significant impact on the total unemployment (UR) and the unemployed population (U), while outward migration (NM) has a short-run effect mainly on the economically active population (EA). The model confirmed that the labour market is indifferent to changes in youth unemployment, a key indicator for forming an effective employment policy. The study's practical significance lies in its potential to inform the government, international organisations, and business communities about the state of the labour market and the necessary vectors of social policy. This will ensure economic growth and improve citizens' quality of life in light of the changing nature of the labour market.
Keywords: 330; labour market; unemployment; employment; migration; workplaces; surplus of personnel; deficit of personnel; digitisation of business processes